FENOMENA GLASS CEILING DALAM JABATAN PIMPINAN TINGGI PRATAMA DI PEMERINTAH KOTA KENDARI - Muhammad Yusuf; Muhammad Ilham Nur Ikhsan Rintaka Rintaka (Journal Publicuho, 2025)
This study aims to examine the phenomenon of the glass ceiling that limits women’s advancement to positions of Primary Leadership in the Kendari City Government. Using a qualitative approach with a case study design, data were collected through in-depth interviews with six civil servants (four women and two men), as well as an analysis of local government policy documents. The findings reveal that although the formal selection process for leadership positions appears gender-neutral, women continue to face barriers stemming from personal, organisational, and socio-cultural factors. The glass ceiling phenomenon in Kendari City is primarily driven by implicit obstacles operating through the interaction between bureaucratic structures and social culture. The study recommends strengthening affirmative policies, implementing mentoring programs, and promoting a more gender-inclusive work culture within the public sector.